Assistance of Handicraft Small Business in Increasing Capacity - Andarita Rolalisasi; Luvia Friska Narulita; Yurie Salsabilla Annoralia; Dika Arfita Nur Karim (IPTEK Journal of Proceedings Series, 2023)
The micro, small and medium enterprises (MSMEs) is important in building the nation’s economy. Our SMEs partners are owned by Architecture Students of Universitas 17 Agustus 1945 Surabaya, they are Keranting and Beelovedthings. Keranting runs in Fashion products with the application of Ecoprint. Ecoprint itself is a process of transferring patterns or colors into fabric/leather/paper media using natural materials and dyes. Meanwhile, Beelovedthings is engaged in handicrafts which are used for souvenirs and merchandise. The partners problems are un-consistent stock of products and they have not reached the turnover target because they are still doing conventional marketing. To overcome these problems, we have to obtain consistent supply of raw materials, availability of adequate equipment that can support the production process, the consistent availability of various types of products, content creation and selection of digital marketing platforms, as well as increasing e-commerce and social media traction. The results of this program are not only in the form of stock fulfillment, but also more varied content creation which can attract more customers. The availability of various digital marketing platforms makes it easier for buyers to reach MSME products with paid promotions carried out on digital marketing platforms to increase eCommerce traction.